Female roles in Euripidean tragedy. Language, performance, conceptions - Ingretolli, F (2022)
The thesis aims to offer a typology of the various ways in which tragic women conceptualize and perform their role in Euripidean tragedy, examining the wide range of female characters’ acts, attitudes, and languages as reflective of their role performances.